The Unstable Voting Behaviour: Tracing of the Voting Behaviour in Indonesia Post-Reformasi Era - Wasisto Raharjo Jati (Sekretariat Jenderal DPR RI, 2021)
Article aimed to analyses about construction of voting behavior in Indonesia election implementation. It urge and significant to elaborate and scrutinize political preferential which became base foundation to elect and submit their vote. There are two prominent factor can be main tools to covering voting behavior trend In Indonesia. Firstly, figures presumably primary sources to mention constructing public voting behavior. In Indonesia post authoritarian era, democracy has been suspended due to emergence of strong figure. This become ironic in implementation of democracy when hijacked oligarchic power that still persist and insist their resources in recent era. Secondly, analyzing of voting behavior in Indonesia has been swiftly in every election. It’s important to note that main character of voting behavior is swing voters dominated by young residents. Therefore, voting behavior trend fluctuated depending on issue and media news, become main consideration public to elect and submit their vote. In addition to both factor, emergence of political broker in recent election has indicated urgent needs to bridging voter and candidate in order to more engage. Those three factor will be primary focus to be elaborated in this paper, how recent trend in voting behavior in Indonesia and its impact to election event.AbstrakArtikel ini bertujuan untuk menganalisis konstruksi perilaku memilih dalam pemilu Indonesia. Isu ini menjadi penting dan siginifikan dalam melihat pola preferensi memilih ketika akan mencontreng kertas suara. Temuan dalam riset ini memuat dua faktor penting yang menjadi basis politik perilaku memilih Indonesia. Pertama, kekuatan personal seorang elite agaknya menjadi faktor penting dalam membaca perilaku memilih tersebut. Hal ini dikarenakan kondisi demokrasi Indonesia yang masih terbajak oleh kekuatan oligarki yang masih cukup kuat. Kedua, masih adanya masa pemilih mengambang, utamanya kalangan muda dan terdidik. Hal tersebut dikarenakan perilaku politik mereka masih dipengaruhi adanya isu dan kepentingan. Di luar dari kedua faktor tersebut, munculnya broker politik dan uang politik menjadi faktor yang tidak bisa terelakan dalam konstruksi perilaku memilih di Indonesia paskareformasi.